2022
DOI: 10.3390/cancers14194809
|View full text |Cite
|
Sign up to set email alerts
|

TFAP2C Knockdown Sensitizes Bladder Cancer Cells to Cisplatin Treatment via Regulation of EGFR and NF-κB

Abstract: Cisplatin is the first-line chemotherapy for advanced or metastatic bladder cancer. Nevertheless, approximately half of patients with BCa are insensitive to cisplatin therapy or develop cisplatin resistance during the treatment process. Therefore, it is especially crucial to investigate ways to enhance the sensitivity of tumor cells to cisplatin. Transcription factor AP-2 gamma (TFAP2C) is involved in cancer development and chemotherapy sensitivity. However, its relationship with chemotherapy has not been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 71 publications
(82 reference statements)
1
9
0
Order By: Relevance
“…Huang et al 42 found that ASB6 attenuates ER stress to increase the stem cell characteristics of oral squamous cell carcinoma cells and enhance their metastatic ability. The transcription factor TFAP2C is involved in tumour development and chemotherapy sensitivity 43 and has potential as a biomarker of treatment resistance in colorectal cancer 44 . The transcriptional modulator Jun dimerization protein 2 (JDP2) is closely related to tumour differentiation and apoptosis and participates in the regulation of CD8+ T cell immune function 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al 42 found that ASB6 attenuates ER stress to increase the stem cell characteristics of oral squamous cell carcinoma cells and enhance their metastatic ability. The transcription factor TFAP2C is involved in tumour development and chemotherapy sensitivity 43 and has potential as a biomarker of treatment resistance in colorectal cancer 44 . The transcriptional modulator Jun dimerization protein 2 (JDP2) is closely related to tumour differentiation and apoptosis and participates in the regulation of CD8+ T cell immune function 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin promotes tumor cell apoptosis by forming an adduct with the DNA of tumor cells, thereby achieving its anti-tumor effect [ 32 ]. Many studies have confirmed that the decrease in cell cycle arrest is the key factor in tumor cisplatin resistance [ 33 , 34 , 35 ]. We found that the overexpression of miR - 660 decreased the cell proliferation capacity and increased the cell apoptosis rate and cell cycle arrest in cisplatin-treated A549/CDDP and CALU-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of tumors to cisplatin is the most critical factor determining the therapeutic effect for cancer patients; cisplatin sensitivity is far more important than the final cumulative dose and dose intensity of cisplatin [ 48 , 49 ]. Some patients are insensitive to cisplatin [ 50 , 51 ], and even higher doses of GC combination chemotherapy cannot completely eliminate drug-resistant micrometastases. To eradicate these micrometastases, the combination of GC with other antitumor drugs can be considered to improve the efficacy of neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%